2016
DOI: 10.1002/cnma.201600264
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Dimeric Precursor Intermediate during the Nonaqueous Synthesis of Titanium Dioxide Nanocrystals

Abstract: For tailoring the size and morphology of nanoparticles, a deep knowledge of the mechanism leading to particle formation is required. We have investigated the reaction mechanisms in the synthesis of anatase nanocrystals by the so‐called benzyl alcohol route as a model for binary metal oxides, and elucidated the chemical structure of cluster species involved in the reaction using NMR spectroscopy and single crystal X‐ray structure analysis. In the first reaction step, a novel dimeric coordination complex is form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Phenomena of formation leading to binary and doped metal oxide nanoparticles were described in several papers ( [29,30] and [31,32], respectively). The mechanisms of secondary particle formation during the nonaqueous synthesis influenced subsequently dispersing [33], functionalization [34,35], or surface property tailoring [36,37].…”
Section: The Aggregation and Agglomeration Of Nanoparticles Dispersedmentioning
confidence: 99%
“…Phenomena of formation leading to binary and doped metal oxide nanoparticles were described in several papers ( [29,30] and [31,32], respectively). The mechanisms of secondary particle formation during the nonaqueous synthesis influenced subsequently dispersing [33], functionalization [34,35], or surface property tailoring [36,37].…”
Section: The Aggregation and Agglomeration Of Nanoparticles Dispersedmentioning
confidence: 99%
“…The transient nature of intermediate species makes their characterization extremely challenging. For example, a recent study by Garnweitner and co‐workers showed the presence of defined oligomeric coordination complexes during the growth of anatase nanoparticles from titanium isopropoxide in benzyl alcohol . Using various NMR spectroscopy techniques and single crystal structure determination they were able to determine several intermediate species including a dimeric titanium benzyloxide [Ti(OBn) 4 (HOBn)] 2 with BnOH representing benzyl alcohol.…”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…Using various NMR spectroscopy techniques and single crystal structure determination they were able to determine several intermediate species including a dimeric titanium benzyloxide [Ti(OBn) 4 (HOBn)] 2 with BnOH representing benzyl alcohol. While this compound formed rather early in the synthesis, it was not recognized as the monomeric species for particle formation, but reacted to [Ti 16 O 16 ](OBn) 32 , which transformed into anatase …”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations